1993
DOI: 10.1161/01.str.24.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of endothelium with dilation produced by inhibitors of cyclic nucleotide diesterases in mouse brain arterioles in vivo.

Abstract: Background and Purpose: In vitro evidence gathered from extracerebral conductance vessels suggests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…However, it is not known if the cGMP response to electrical stimulation or SNP is specifically localized to vascular smooth muscle. cGMP鈥恉ependent vasodilation of arterioles has been reported in rat cremaster muscle [20]and other tissues [21, 22]. We also find that the arteriolar response to contraction in cremaster muscles from mdx mice was attenuated, providing physiological evidence consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is not known if the cGMP response to electrical stimulation or SNP is specifically localized to vascular smooth muscle. cGMP鈥恉ependent vasodilation of arterioles has been reported in rat cremaster muscle [20]and other tissues [21, 22]. We also find that the arteriolar response to contraction in cremaster muscles from mdx mice was attenuated, providing physiological evidence consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have also shown the dilatory effects of dipyridamole as more or less selective phosphodiesterase inhibitors on intact cerebral arteries (Harris et al, 1989;Cosentino et al, 1992;Parfenova et al, 1993;Rosenblum et al, 1993;Willette et al, 1997). The present study demonstrated that dipyridamole induced only small changes in [Ca 2+ ]i in testicular or cerebral arteriole smooth muscle cells, and no dilation was observed in these arterioles.…”
Section: Response Of Smooth Muscle Cells In Testicular and Cerebral Asupporting
confidence: 68%
“…In studies on animals, most nonselective and selective PDE inhibitors induce cerebral artery dilatation, although with different potency depending on species and vessels tested. Selective PDE3 inhibitors show effective endothelial independent relaxation, whereas PDE1, PDE4, and PDE5 inhibitors elicit endothelial-dependent relaxation (Kruuse et al, 2001;Parfenova et al, 1993;Rosenblum et al, 1993). The headache was scored on a verbal scale from 0 to 10; accompanying symptoms were graded none, minor, moderate, or severe.…”
Section: Cyclic Nucleotides Phosphodiesterases and Cerebral Vasodilmentioning
confidence: 99%